ANALYSIS OF INTERNAL EFFECT ON CORPORATE VALUES WITH EXCHANGE RATE AS MODERATED VARIABLES (Case Study of Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2014-2018) - Erniwati Erniwati; Cepi Pahlevi; Andi Aswan (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
This study aims to analyze the effect of profitability, sales growth, capital costs, and asset growth on firm value, and analyze the exchange rate moderating the effect of profitability, sales growth, capital costs, and asset growth on firm value. The sample used is the Food and Beverage sub-sector companies listed on the Stock Exchange totaling 12 companies, data collection techniques through observation and websites. Data analysis techniques using moderate regression analysis (MRA). The findings show that ROA has a significant and positive effect on firm value, WACC has a significant and negative effect on firm value, sales growth has no effect on firm value, asset growth has no effect on firm value. The exchange rate against company value is not significant, while the moderating variable of the exchange rate moderates the relationship between the effect of profitability on company value, the exchange rate that moderates the relationship between the effect of capital costs on company value, the exchange rate does not have the potential to be a moderating variable that affects the strength of the relationship between growth variables sales with the value of the company, and the exchange rate does not have the potential to be a moderating variable that affects the strength of the relationship between the variable growth of assets with the value of the company.